Climate‐driven sea level anomalies modulate coastal groundwater dynamics and discharge. Issue 11 (3rd June 2013) - Gonneea, Meagan Eagle; Mulligan, Ann E.; Charette, Matthew A.
Abstract [1] To better understand the physical drivers of submarine groundwater discharge (SGD) in the coastal ocean, we conducted a detailed field and modeling study within an unconfined coastal aquifer system. We monitored the hydraulic gradient across the coastal aquifer and movement of the mixing zone over multiple years. At our study site, sea level dominated over groundwater head as the largest contributor to variability in the hydraulic gradient and therefore SGD. Model results indicate the seawater recirculation component of SGD was enhanced during summer while the terrestrial component dominated during winter due to seasonal changes in sea level driven by a combination of long period solar tides, temperature and winds. In one year, sea level remained elevated year round due to a combination of ENSO and NAO climate modes. Hence, predicted changes in regional climate variability driven sea level may impact future rates of SGD and biogeochemical cycling within coastal aquifers.